Teacher's Strategy in Improving Student's Motivation Learning the Art of Reading the Qur'an: Strategi Guru dalam Meningkatkan Motivasi Siswa Belajar Seni Baca Al-Qur’an - Amin, Khoirul (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to (1) determine the teacher's strategy to increase student motivation in learning the art of reading the Qur'an. (2) knowing the supporting and inhibiting factors that influence the teacher's strategy in increasing student motivation in learning the art of reading the Qur'an. This study uses a qualitative approach. data collection using participant observation, in-depth interviews, and documentation studies. data analysis technique using descriptive qualitative. The results of the study show that there are 4 teacher strategies to motivate students in learning the art of reading the Qur'an, namely (1) Giving examples of successful figures in the field of reading the Qur'an. (2) Explaining the goals and advantages of learning the art of reading the Qur'an. (3) Giving appreciation in the form of appreciation to students. (4) Provide direction for students who have difficulty. Meanwhile, there are 4 supporting factors in motivating students to learn the art of reading the Qur'an, namely (1) Students' self-interest. (2) Family support. (3) Facilities and infrastructure. (4) The influence of friends in learning the art of reading the Qur'an. While the inhibiting factors in motivating students to learn the art of reading the Qur'an are (1) lack of self-confidence. (2) Lack of openness to the problems encountered while learning the art of reading the Qur'an. (3) The influence of friends who are not good. (4) the lack of teachers who are experts in the art of reading the Qur'an.